Penyelenggaraan Pesantren Dalam Rangka Memberdayakan Masyarakat - Junaidi, Muhammad (JURNAL USM LAW REVIEW, 2022)
The purpose of this research study is to understand the extent to which the implementation of Islamic boarding schools through the strengthening contained in Law Number 18 of 2019 concerning Islamic Boarding Schools. This is very important and is not only interpreted as a form of state intervention but also makes pesantren capable of strengthening in the context of community empowerment. Through a normative juridical approach, it is hoped that this study will be able to see a careful perspective on existing problems related to the implementation of Islamic boarding schools in the context of empowering the community. The method used is normative juridical. The results of the study show that in order to achieve these goals, pesantren should balance it through strengthening the curriculum. In addition, pesantren must also prepare derivative regulations in accordance with the provisions in Law Number 18 of 2019 concerning Islamic Boarding Schools and their derivative regulations.    Tujuan dari pengkajian penelitian ini adalah untuk mamahami sejauh mana penyelenggaraan pesantren melalui penguatan yang terdapat dalam Undang-Undang Nomor 18 Tahun 2019 tentang Pesantren. Hal ini sangatlah penting yang bukan hanya dimaknai sebagai bentuk intervensi negara akan tetapi menjadikan pesantren mampu melakukan penguatan dalam rangka pemberdayaan masyarakat. Melalui pendekatan yuridis normatif diharapkan kajian ini mampu melihat perspektif secara cermat atas masalah yang ada terkait penyelenggaraan pesantren dalam rangka memberdayakan masyarakat. Metode yang digunakan adalah yuridis normatif. Hasil penelitian menunjukkan untuk mencapai tujuan itu semua maka sudah semestinya pesantren mengimbanginya melalui penguatan kurikulum. Selain itu pesantren juga haruslah menyiapkan peraturan turunan sesuai dengan ketentuan dalam Undang-Undang Nomor 18 Tahun 2019 Tentang Pesantren dan peraturan turunannya.